Analog Video in Moving Image Archives & Conservation: Infrastructures of Knowledge from Production to Preservation. Issue 1 (29th November 2018) - Sorensen, Lauren
The essay uses a set of theoretical ideas offered by Susan Leigh Star to argue for a shift in contemporary understandings of, and approaches to, video preservation. Instead of focusing on the granular characteristics of tape and their material stability, I argue, the audiovisual archival community should view preservation as a set of linked systems that function within a web of shifting perspectives and context-driven solutions.